Temperature changes in Southeast Asia: 1973-2008 - Suree Chooprateep (2018)
This paper studied the monthly seasonally-adjusted surface temperature patterns in Southeast Asia from 1973 to 2008. The study area comprised 40 regions of 10° by 10° grid-boxes in latitudes 25°S to 25°N and longitudes 75°E to 160°E. The data were fitted with a second-order auto-regressive process to reduce auto-correlations at lags 1 and 2 months. Factor analysis was used to account for spatial correlation between grid-boxes, giving six contiguous layer regions that extended beyond the original study area to form larger regions. Exploration extended from latitudes 35°S to 25°N and longitudes 65°E to 160°E. Multivariate linear regression models were then fitted to data within these larger regions. Temperatures were found to have increased in all regions, with the increases ranging from 0.091 to 0.240°C per decade.